INVESTING IN PERSONALITY DEVELOPMENT AS THE MOST VALUABLE ASSET OF LONG-TERM COMPETITIVENESS OF THE ENTERPRISE (INNOVATIVE ECONOMY, 2020)
Hurman О.М., Tserklevych V.S. INVESTING IN PERSONALITY DEVELOPMENT AS THE MOST VALUABLE ASSET OF LONG-TERM COMPETITIVENESS OF THE ENTERPRISEPurpose. The aim of the article is a scientific argumentation of the priority of investing in personal development as the most valuable asset of long-term competitiveness of the enterprise.Methodology of research. The following general research methods are used in the article to achieve this goal and solve research problems,: logical analysis, comparison, systematization - to substantiate the relevance of comprehensive personal development and the formation of relevant competencies in the context of innovative practice of assessing individual employee value; reflection of Ukraine's position on the Global Competitiveness Index for 2014-2019; identification of goals and objectives of the personnel development system; theoretical generalization - to characterize the essence and place of personal development in the content of modern concepts of personnel management of the enterprise; graphical representation of materials - to reflect the integrated indicator of human capital in terms of psychology of happiness (human self-realization), the basic components of the personnel management system, features and functions of personnel management services in foreign countries.Findings. The article is devoted to the analytical understanding of the most pressing problem in the field of personnel management — the effective development of the employee's personality. The essence and place of personal development in the content of modern concepts of personnel management of the enterprise are characterized. The relevance of comprehensive personal development and the formation of relevant competencies in the context of innovative practices of assessing the individual value of the employee are substantiated. The foreign experience of personnel development, first of all — the managerial level — as a priority function of the personnel management service is presented in an annotation. It is investigated that the definition of personnel development priorities should be carried out in two directions: by determining the priority of the goals of personnel policy of personnel management of the enterprise; by determining the priority or severity of individual problems within the existing human capital system that meet the objectives of the enterprise. It is recognized that the main source of stability and long-term competitiveness in the market is knowledge of the abilities and capabilities of its employees, creating a favourable environment for the growth of staff competence and its comprehensive development.Originality. According to the results of the study it is argued that the main source of stability and long-term competitiveness of the enterprise in the market is knowledge of the abilities and capabilities of its employees, creating a favourable environment for staff competence and systemic professional development. The content and functions of personnel management services are systematized on the example of multinational corporations of the world. The basic components of the personnel management system in the general system of corporate governance are specified. An integrated indicator of human capital from the point of view of the psychology of happiness (human self-realization) has been formed.Practical value. The obtained results of the research can be used by top managers of service economy enterprises in Ukraine to determine the priority of investment measures in the development of their employees.Key words: personality, development, motivation, diagnostics, personnel department, personnel management service, career chart.
Keywords: Key words; personality; development; motivation; diagnostics; personnel department; personnel management service; career chart.